Assessment of broiler surface temperature variation when exposed to different air temperatures - Nascimento, G. R.; Nääs, I. A.; Pereira, D. F. [UNESP]; Baracho, M. S.; Garcia, R. (FapUNIFESP (SciELO), 2011)
This study was conducted to determine the effect of the air temperature variation on the mean surface temperature (MST) of 7- to 35-day-old broiler chickens using infrared thermometry to estimate MST, and to study surface temperature variation of the wings, head, legs, back and comb as affected by air temperature and broiler age. One hundred Cobb® broilers were used in the experiment. Starting on day 7, 10 birds were weekly selected at random, housed in an environmental chamber and reared under three distinct temperatures (18, 25 and 32°C) to record their thermal profile using an infrared thermal camera. The recorded images were processed to estimate MST by selecting the whole area of the bird within the picture and comparing it with the values obtained using selected equations in literature, and to record the surface temperatures of the body parts. The MST estimated by infrared images were not statistically different (p > 0.05) from the values obtained by the equations. MST values significantly increased (p < 0.05) when the air temperature increased, but were not affected by bird age. However, age influenced the difference between MST and air temperature, which was highest on day 14. The technique of infrared thermal image analysis was useful to estimate the mean surface temperature of broiler chickens.
Keywords: Image analysis; Poultry; Thermal comfort